2011
DOI: 10.1096/fj.11-188607
|View full text |Cite
|
Sign up to set email alerts
|

PPARα and PPARγ protect against HIV‐1‐induced MMP‐9 overexpression via caveolae‐associated ERK and Akt signaling

Abstract: Activation of matrix metalloproteinase-9 (MMP-9) is involved in HIV-1-induced disruption of the blood-brain barrier (BBB). In the present study, we hypothesize that peroxisome proliferator-activated receptor (PPAR)-α or PPARγ can protect against HIV-1-induced MMP-9 overexpression in brain endothelial cells (hCMEC cell line) by attenuating cellular oxidative stress and down-regulation of caveolae-associated redox signaling. Exposure to HIV-1-infected monocytes induced phosphorylation of ERK1/2 and Akt in hCMEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…MMP-9 gene expression is primarily regulated at the transcriptional level via transcription factors such as NF-κB and STAT3 [7,10]. Mutation of NF-κB binding sites decreased the activity of MMP-9 promoter in endothelial cells and A549 cells [26,27]. In our study, LPS enhanced the phosphorylation of NF-κB.…”
Section: Discussionsupporting
confidence: 48%
“…MMP-9 gene expression is primarily regulated at the transcriptional level via transcription factors such as NF-κB and STAT3 [7,10]. Mutation of NF-κB binding sites decreased the activity of MMP-9 promoter in endothelial cells and A549 cells [26,27]. In our study, LPS enhanced the phosphorylation of NF-κB.…”
Section: Discussionsupporting
confidence: 48%
“…PPARγ2 activation reduces the production of macrophage and lymphocyte cytokine, inhibits the growth, proliferation [62], [63], and migration of vascular smooth muscle cell as well as restrains the expression of endothelial cell adhesion molecule, chemokine, and matrix metalloproteinase [64]. All of these evidences suggested that PPARγ2 is benefit to prevent the initiation of atherosclerosis [65].…”
Section: Discussionmentioning
confidence: 95%
“…For example, IRF-3 transactivates expression of proinflammatory cytokines and chemokines, including IL-6, MIP-1α, and RANTES (Sweeney et al 2010), which are known to contribute to the disruption of BBB integrity (Terao et al 2008; Toborek et al 2003). Activated IRF-3 can also stimulate expression of matrix metalloproteinases (MMPs) (Sweeney et al 2010), which were shown to be involved in proteolytic degradation of tight junction proteins (Huang et al 2011). …”
Section: Discussionmentioning
confidence: 99%